Science and sustainable food security selected papers of M S Swaminathan - Swaminathan, Monkombu Sambasivan (IISc centenary lecture series ;, 2010)
This book provides a roadmap for achieving sustainable agricultural advance and food security in an era of climate change and global economic melt-down. The contents include a description of the paradigm shift under the leadership of the author, from a green to an ever-green revolution necessary for advancing productivity in perpetuity without ecological harm. Science and Sustainable Food Security shows many methods of linking ecological security with livelihood security, and provides a scientific basis for entering an era of biohappiness based on the sustainable and equitable use of biodiversity. Also, methods of adaptation to the impact of global warming are described. This book will prove invaluable to all interested in sustainable human security and happiness.